Avaliação dos processos de produção de protease fibrinolitica por fermentação submersa, semi-sólida e extrativa utilizando uma espécie de bacilo da Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The fibrinolytic proteases degrade fibrin clots and therefore play an important role in the pharmaceutical industry as chemotherapeutic agents in the treatment of cardiovascular diseases. These biocatalysts were gradually discovered from plants, insects, earthworms, snakes and microorganisms (bacteria and fungi). Cardiovascular disease has been one of the leading causes of death in the world. A major cause of heart disease is the accumulation of fibrin in the arteries, causing thrombosis. According to the World Health Organization (WHO), about 17.5 million people will die of cardiovascular disease this year, and in 2030, this amount will be 23.6 million. Given the great potential of microbial biodiversity and the growing regional Amazon applicability of enzymes in the production of drugs, this research was conducted with the objective to (1) evaluate the growth of Bacillus stearothermophilus, (2) establish growth parameters associated with production of fibrinolytic proteases in submerged fermentation and (3) assess the effect of the extractive fermentation in the separation of these enzymes. In this study techniques of extractive fermentation and solid-state fermentation were employed. By submerged fermentation the following parameters were determined: Profile of growth of Bacillus stearothermophilus and the production of protease using 100 mL of the liquid medium [(g / L) 2 g KH2PO4, (NH4)2SO4 1 g, MgSO4 7H2O 0,1 g Na2HPO4 2H2O 0,9 g, yeast extract 1 g, distilled water 1000 ml] pH 7.2 supplemented with 0.5% gelatin in an 500 mL Erlenmeyer flask. The growth of the bacteria was determined at 610 nm, once every 2 hours for 36 hours. To determine the best conditions for the production of proteases were evaluated the influence of pH, stirring and temperature, age of inoculum and substrate concentration, the influence of natural sources of carbon (tapioca, arraruta and crueira), nitrogen sources and aeration. In the recovered extract was also performed a toxicity bioassay in Artemia salina and degradation tests in vitro of the blood clot by the fibrin plate method and the artificial clot degradation in tube. In addition, the partition coefficient (K), the purification factor (PF) and recovering the enzyme were determined. The solid-state fermentation was performed using as substrate 10g of manteiguinha bean [Vigna unguiculata (L.) Walp] with 60% humidity, pH 5.0 in a 250 ml Erlenmeyer flask. In extractive fermentation the best conditions were pH 5.0, 180 rpm and 25 °C in systems using PEG 1000 (g/mol-1) to 20% (w/w) and phosphate salts 15% (w/w) with K 1.05; FP 1.00; 152.54 Y. 34 mm halo in fibrin plate and partial degradation of the clot in tube. In the solid-state fermentation, the production of protease was 8.87 (U/mL), 23 mm of translucent halo in fibrin plate with total degradation of the blood clot in 24 hours. In this study, protease produced from Bacillus stearothermophilus by extractive fermentation and semi-solid fermentation was evaluated, showing in the optimum cultivation conditions that this microorganism presents physiology for industrial application in the production of the fibrinolytic protease
Keywords: Protease fibrinolitica; Fermentação submersa; Fermentação semi-sólida; Fermentação extrativa; Bacilo da Amazônia; Fibrinolytic proteases; Submerged fermentation; Solid-state fermentation; Extractive; Bacillus Amazon; CIÊNCIAS BIOLÓGICAS